Partnerships between medical centres and general hospitals providing normal care standards in gynaecology and obstetrics in Germany = Partnerschaft zwischen Häusern der Maximalversorgung und Häusern der Grund- und Regelversorgung in der Gynäkologie und Geburtshilfe in Deutschland - Schütz, Florian; Maleika, Annette; Pöschl, Johannes; Domschke, Christoph; Seitz, Helmut K.; Beuter-Winkler, Petra; Sohn, Christof (Geburtshilfe und Frauenheilkunde, 2012)
Hospital managers and the heads of medical departments are nowadays being faced with ever increasing demands. It is becoming difficult for some small hospitals to find highly experienced or even experienced medical staff, to provide specific health-care services at break-even prices and to maintain their position in competition with other hospitals. On the other hand, large hospitals are facing enormous pressure in the investment and costs fields. Cooperation could provide a solution for these problems. For an optimal strategic exploitation of the hospitals, their direction could be placed in the hands of a joint medical director. However, the directorship of two hospitals is associated both with opportunities and with risks. The present article illustrates the widely differing aspects of the cooperation between a medical centre and a general hospital providing standard care from both a theoretical point of view and on the basis of practical experience with an actual cooperation of this type in Heidelberg.